A reference architecture for integrating the Industrial Internet of Things in the Industry 4.0 - Radanliev, P; de Roure, D; Nicolescu, R; Huth, M (2019)
This paper presents a new reference architecture model for the integration of these systems and technologies. The reference architecture model is based on grouping of future and present techniques and presenting the design process through a new hierarchical framework and a new cascading model. With the application of the grounded theory, the hierarchical framework and the cascading model detail a new process for creating a taxonomy of categories and grouping of concepts into integration design. The new design process is tested and versified with an empirical review of Industry 4.0 frameworks and results with a new 5 levels reference architecture step by step model for the integration of these related systems and technologies (Industrial Internet of Things, Cyber Physical Systems, and Industry 4.0).